Use of extracellular polymeric substances as natural redox mediators to enhance denitrification performance by accelerating electron transfer and carbon source metabolism. (February 2022) - Wang, Xianbao; Chen, Tiantian; Gao, Chuyue; Xie, Yili; Zhang, Anlong
Graphical abstract: Highlights: EPS could be used as redox mediators to enhance denitrification performance. EPS addition accelerated the electron transfer and improved the activity of enzymes. EPS mainly played a similar role to that of quinone loop in electron transfer chain. EPS addition enhanced glucose metabolism to increase available NADH yield. Abstract: Extracellular polymeric substances (EPS) extracted from waste activated sludge were used as endogenous redox mediator to enhance denitrification performance. The nitrate reduction rate increased 1.42-fold when EPS were added at 75 mg C/L (C represents total organic carbon). EPS addition decreased the charge transfer resistance and improved the electron transport system activity. The nitrate reductase and nitrite reductase activities improved by 29.7% and 25.4%, respectively. The activation energy of the system with EPS addition (25.82 kJ/mol) was 31.1% lower than that of the control group (37.49 kJ/mol). Besides, EPS could be used as electron carriers to accelerate electron transport; its primary role was similar to that of the quinone loop in the electron transfer chain. More importantly, EPS addition enhanced carbon source metabolism, which increased the available nicotinamide adenine dinucleotide yield to 1.21 times that of the control group, and thus promoted the denitrification performance of activated sludge.